Masterworks of George Enescu : a detailed analysis - Bentoiu, Pascal (Scarecrow Press, 2010)
Masterworks of George Enescu provides a profound and very detailed analysis of more than 25 of this important composer's most representative works. Translated from musicologist Pascal Bentoiu's Romanian publication, Lory Wallfisch presents this vital work for the first time to English-speaking audiences, providing the worldwide public with the tools to understand and enjoy Enescu's music.